Russian loanwords in the Oxford English Dictionary revisited - Podhajecka, Mirosława (Przegląd Rusycystyczny, 2018)
This study revisits Russian loanwords in the third edition of the Oxford English Dictionary (henceforth, OED3) in order to discuss their lexicographic treatment, including the quality of etymological references. Arguments behind the choice of this dictionary are clear-cut: not only is OED3 the most exhaustive dictionary of English, but it also offers the fullest etymological analysis of the whole of the lexis of English available anywhere. Space restrictions preclude the inclusion in the dictionary every word of Russian origin in English texts. In the past, lexical items had to occur in at least five different sources to ensure inclusion, whereas the frequency necessary to include a word into OED3 today is reckoned in hundreds or even thousands.